The Absorption, Distribution, and Excretion of 18 Elements of Tibetan Medicine Qishiwei Zhenzhu Pills in Rats with Cerebral Ischemia. (28th December 2021) - Song, Yinglian; Fu, Ke; Zhang, Dewei; Xu, Min; Wu, Ruixia; Xiong, Xueqing; Liu, Xianwu; Wu, Lei; Guo, Ya; Zhou, You; Li, Xiaoli; Wang, Zhang
Abstract : The aim of this study is to determine 18 elements in Tibetan medicine Qishiwei Zhenzhu pills (QSW) and their absorption, distribution, and excretion in rats with cerebral ischemia. Microwave digestion and inductively coupled plasma mass spectrometry (ICP-MS) were used to determine 18 elements of QSW in simulated gastrointestinal (GI) juice. Rats were given QSW (66.68 mg/kg) followed by middle cerebral artery occlusion (MCAO). Sham rats received saline and were not subjected to MCAO. ICP-MS was applied to determine the content of 18 elements in hepatic venous blood, abdominal aortic blood, brain, liver, kidney, hair, urine, and feces 24 h after MCAO. In vitro results showed that the extraction rate of Mn, Cu, Sr, Pb, Au, and Hg of QSW in gastric juice (1 h) was higher than that in water, and the contents of Cu, Au, Sr, and As were higher in intestinal juice (4 h) than in water. In vivo results showed that the contents of elements in the blood were quite low, and QSW increased Ni, Cr, Sr, Co, and V in artery blood and decreased V in venous blood. Elements in the tissues were also low, and QSW increased brain Li but decreased Cr and Cd; QSW increased kidney Ag and Cs and liver Mn but decreased liver Ni. QSW increased urinary excretion of Li, Sr, Hg, Cs, and V; QSW increased Hg content in hair but decreased Ni. Stool is the main excretion pathway of the elements in QSW, with Ba, Mn, Sr, Cd, V, Cu, Cs, Li, Pb, Ag, Hg, Cr, As, and Co the highest. In summary, this study examined the distribution of 18 elements in QSW-treated MCAO rats. The accumulation of these elements in blood and tissues was extremely low, and the majority was excreted in feces within 24 h, highlighting the importance of the gut-microbiota-brain axis in QSW-mediated brain protection.